Forskarskola i kulturhistoriska studier - Sanner, Inga (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The Research School of Studies in Cultural History started in 2010 and is financed by the Faculty of Humanities at Stockholm University. The school has accepted 19 PhD students from different disciplines within the faculty and it is led by a steering committee with representatives from various disciplines. The aim of the school is to find new interdisciplinary ways to study history and to create new intellectual milieus and to investigate new forms of cooperation within the PhD programs. The activities of the school, such as courses, seminars, guest researchers etcetera, have proven successful so far. Problems that have occurred are linked with the fact that the PhD students sometimes have been torn between the activities of the research school and the curriculum of their respective departments.